The Application of Learning through a Scientific Approach based on Project-based Learning with Hots Orientation - Kristina, Nova (Lembaga Bale Literasi, 2023)
The 2013 curriculum is a national curriculum that has been developed by the Ministry of Education and Culture with the aim of preparing students to have productive, creative, innovative and affective learning skills and be able to contribute to the life of society, nation and state. However, in practice,there are still some difficulties such as material and assignments that are not in accordance with the background of students. In addition, this curriculum still focuses on mastering cognitive knowledge which is more concerned with memorizing material. Thus the students' thinking processes are still at level C1 (remembering), understanding (C2), and C3 (application). This study aims to (1) find out the application of HOTS-oriented PBL (Problem Based Learning) learning in English with procedural text in class XII TKR B at SMK Negeri 3 Tuban, and (2) find out the increase in English learning outcomes with procedure text material in class XI TKJ at SMKN 1 Kikim Tengah using the HOTS (Higher Other Thinking skills) oriented PBL (Problem Based Learning) model. The learning media used are laptops, LCD projectors, videos, power point, while the tool used is the Conventional Brake System Trainer Instrument with data collection techniques using the Problem BASED Learning model. As for the results and discussion, they will be discussed further in the results and discussion section.